Inhibition of non-small-cell lung cancer cell proliferation by Pbx1 - Li, Weihao; Huang, Kai; Guo, Haizhou; Cui, Guanghui; Zhao, Song (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Lung cancer is one of the most deadly human cancers and continues to be a major unsolved health problem worldwide. Here, we evaluate the function of Pbx1 in the proliferation of non-smallcell lung cancer (NSCLC). In contrast with its known proliferative function, we found that Pbx1 inhibits the proliferation of lung cancer cells. In particular, Pbx1-specific RNA interference resulted in increased proliferation in lung cancer cells. In addition, histone H3 phosphorylation was also increased following inhibition of Pbx1 expression. In contrast, Pbx1 overexpression repressed the proliferation of lung cancer cells and inhibited DNA synthesis. Collectively, our data indicate that Pbx1 inhibits proliferation in lung cancer cells, suggesting a complex role for Pbx1 in modulating the proliferation of cancer cells and making this protein a potential new target for lung cancer therapy.